(untitled) (Research, Society and Development, 2022)
The role of Nurses in the Area of Women’s Health grows every day and gains a significant space with regard to the care and monitoring of women at all stages of life. What is the perception of pregnant women about the Nurse’s assistance during prenatal care? This is an integrative review research consolidated through a bibliographic study, using the following keywords: “prenatal”, “pregnant women’s perception”, “assistance” and “guidance”. Only articles in Portuguese were selected, with full texts, in the LILACS, SciELO and BDENF databases, which addressed the proposed theme and were dated from 2018 to 2021. Data collection was carried out from September 2021 to May de 2022. Through the research, it was observed that most studies aimed to assess the perception of pregnant women about the nurse’s care, as well as describe the care provided by this professional during prenatal care. According to the selected studies, it was noticed that the pregnant women were satisfied with the care provided by the nurse at this stage of pregnancy and their understanding of the importance of performing prenatal care in a qualified way.